The role of cash waqf in rejuvenation of Malaysian waqf assets - Anwar bin Allah Pitchay (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
The motivation of the study arises out the concern for the current state of affairs of Malaysian Waqf assets development. Various findings revealed that the Malaysian government mainly funds the development of Waqf in Malaysia. This therefore poses a threat to the sustainability of Waqf development because the government funding for Waqf development has been dwindling over the years. Hence, Waqf assets lack liquidity for development. Therefore, this study looks at the possibility of rejuvenating the role of Waqf in Malaysia by the Waqf institutions through cash Waqf to address the liquidity problem. However, various factors can influence Muslims to contribute cash Waqf. In addition, lack of attractive and inconvenient models of cash Waqf can demotivate Muslims' to contribute cash Waqf. In this study, we proposed a new cash Waqf model where Muslim employees and, Islamic businesses and institutions (MEIBI) model, can contribute periodically for the sustainability of the liquidity supply. The first part of the study describes and proposes the MEIBI model. This model is a combination of employees salary deduction and corporate philanthropy schemes in form of CSR. The second and third objectives of the study assess the behavioural intention of Muslim employees and IBIs to contribute cash Waqf respectively. These objectives are divided into two essays. The first focuses on examining the behavioural intention of Muslim employees to contribute cash Waqf through employee salary deduction. Theory of Reasoned Action (TRA) developed by Ajzen and Fishbein (1980) is used to examine the behavioural intention of Muslim employees in this regards. Two propositions, i.e. Attitude and Subjective Norm to contribute cash Waqf are developed based on the TRA framework and analysed using structural equation modelling. The findings show attitude and subjective norms of the Muslim employees do have the potential to influence Muslim employees behavioural intention to contribute cash Waqf through employee salary deduction. The second essay examines the behavioural intention of IBIs to contribute cash Waqf. Theory of Planned Behaviour (TPB) developed by Ajzen (1985) is used to examine the propositions. Four main variables, i.e. economic attitude, political pressure, perceived behavioural control and personal moral obligation were tested and analysed using structural equation modelling. The findings show the first three variables significantly influence the behavioural intention of the top management to contribute cash Waqf. Nonetheless, personal moral obligation of the top management was found to be insignificantly. In conclusion, the present study finds that the MEIBI model as proposed in this study has the potential to generate cash Waqf and provide a positive impact on the development of Waqf in Malaysia.